Access to Finance for Female-led Micro, Small and Medium-sized Enterprises in Bosnia and Herzegovina - Qasim, Qursum (World Bank, Washington, DC, 2018)
Female-led Micro, Small, and Medium-Sized Enterprises (MSMEs), play a vital role as job creators, driving female participation in the economy, and boosting inclusive GDP growth. In addition to the direct economic impact of MSMEs, research shows that female-led enterprises employ more women, and that increased control over resources by women leads to improved health and education outcomes for children, among other socioeconomic benefits. Reducing poverty and boosting inclusive growth are therefore directly linked to the economic participation of women in general and women-led MSMEs. Gender equality, while essential and desirable on its own merits, also yields well-documented economic benefits channeled through female labor force participation and, relatedly, through women’s participation in entrepreneurship and leadership in MSMEs. Social norms, difficulties in balancing work and family time demands, and limited access to collateral, among an array of other multidimensional barriers, result in a low percentage of female-owned MSMEs among all MSMEs and constraints in realizing their full potential. Women-led enterprises are more likely to be smaller, informal, and home-based. The World Bank Gender Strategy identifies the multidimensional constraints that hold back women’s participation. Globally, female-owned MSMEs are 38 percent or less of all MSMEs, they are more likely to be smaller, informal, and home-based. They are concentrated in services like health, social work, hairdressing, and beauty treatment. Sectors dominated by women entrepreneurs show lower growth in value-added and turnover.